Murder the truth [large type] : fear, the First Amendment, and a secret campaign to protect the powerful - Enrich, David, 1979- (Mariner Large Print, an imprint of HarperCollins Publishers, 2025)
"In 2019, Justice Clarence Thomas raised the prospect of overturning the legendary New York Times v. Sullivan decision. Though hardly a household name, Sullivan is one of the most consequential free speech decisions ever, enabling journalists to hold the wealthy, powerful, and corrupt to account. With Thomas's words, an idea that had been fomenting on the conservative fringe for years went mainstream. The goal of this movement is simple: to change the laws and the First Amendment to make it harder to scrutinize and critique powerful institutions and individuals. Indeed, many of the same businesspeople, politicians, lawyers, and activists are already weaponizing the legal system to intimidate and punish journalists and others who dare criticize them. In this masterwork of investigative reporting, acclaimed journalist David Enrich traces the roots and reach of this growing threat to our modern democracy -- and lays bare the stakes of losing our most sacrosanct rights." --